Revolutionizing Aluminum-Based Composites: Enhancing Strength with Eggshell and Bagasse Ash Reinforcement via Stir Casting - C P Vandana; Sruthi P.; Jain Alok; Bhati Savita; Praveen; Mohammad Q. (E3S Web of Conferences, 2024)
The study explores a novel approach to enhance the strength of aluminum-based composites by incorporating eggshell and bagasse ash reinforcement through stir casting. The alloy melting process occurred within a muffle furnace, reaching a temperature of 690°C to ensure complete liquefaction. Eggshell and bagasse ash particles were gradually introduced into the molten alloy, while stirring at 480 rpm, ensuring uniform dispersion over 14 minutes. The addition of 4% eggshell and 2.5% bagasse ash led to significant improvements across various mechanical properties. Tensile strength experienced a notable enhancement of approximately 17.89%, while hardness showcased a remarkable increase of approximately 24.66%. Furthermore, fatigue strength demonstrated a significant improvement of approximately 19.56%, and wear resistance exhibited a significant enhancement of approximately 23.8%.These findings underscore the efficacy of eggshell and bagasse ash reinforcement in bolstering the mechanical performance of aluminum-based composites. Such advancements hold promise for diverse applications, from structural components to wear-resistant coatings, offering sustainable and cost-effective solutions in materials engineering.